Strategi Komunikasi Pemkot Depok Dalam Kampanye 3R Melalui Bank Sampah Menuju Lingkungan Yang Bersih Dan Sehat - Wulandari, Yulianti Fajar; Bastian, Yan; Murtiadi, Murtiadi; Afianto, Heri (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The research objective is to explain and evaluate the Depok City Government's communication strategy in the 3R campaign through the Waste Bank to create a clean and healthy environment. This research uses a qualitative approach with a case study design to explore the Depok City Government's communication strategy in the 3R campaign through the Waste Bank. Primary data was obtained through in-depth interviews and FGDs with City Government officials, Waste Bank managers and the community, while secondary data was taken from official documents and media publications. Data was analyzed using thematic analysis techniques to identify key themes, patterns and relevant relationships, providing a comprehensive picture of the success of the 3R campaign in Depok. The result of this work is that the Depok community's awareness of the importance of 3R has increased significantly with active participation in seminars, workshops and training organized by the Depok City Government. The effectiveness of the Waste Bank and the use of social media and information technology has succeeded in reducing the amount of waste in landfills and empowering the community in managing household waste. Collaboration between the City Government, the private sector and local communities through CSR support and active participation of environmental communities has had a positive impact. Regular evaluation and improvement of infrastructure is a priority for the Depok City Government, with incentives and rewards to encourage community participation, ensuring the sustainability of the 3R program.